CORRELATION TYPES OF COMPOUNDS - Hakimova Marguba (TADQIQOTLAR, 2025)
Abstract The study of compound words within the framework of correlation with free word-groups  offers  a  comprehensive understanding of the systemic  and  productive nature of English word-formation. This article focuses primarily on adjectival-nominal compounds as one of the most productive and semantically motivated categories. By analyzing their structural patterns and their semantic correspondence with syntactic constructions,  the  article  demonstrates  how  such  compound  units  are  formed  and function in modern English. The research highlights the role of lexical valency and semantic compatibility between components in the process of compound formation. The  analysis  is  aimed  at  revealing  the  mechanisms  behind  the  construction  of compound adjectives and understanding their syntactic and semantic roots.